COPING BEHAVIOR AND LIFESTYLE PRACTICES OF SEAFARERS’ WIFE - Sablas, Karen G (LIFE: International Journal of Health and Life-Sciences, 2017)
This study was conducted to determine the coping behaviours and life practices of seafarer’s wife. Based on the results, generally the seafarer’s wife-respondents were 41 to 50 years old, Roman Catholic, college level, married for more than six (6) years, with 1 dependent, self-employed and with more than 20,000 pesos income; The seafarer’s wife have a very high degree of practice of the common coping behaviour during the family recreation, work and religious activities; and high degree during community involvement activities; They have a very high extent of coping behaviour in terms of the emotional aspect; and high extent in terms of the social and spiritual aspect; When grouped according their age, number of dependent / children, length of married years, occupation, income and religion, there was no significant difference between their degrees of practice of the common coping behaviour as well as between their extents of coping behaviour during the departure of the husband; however when grouped according to educational attainment, there were significant differences; There was a very high significant relationship between the degrees of practice of the common coping behaviours of seafarers’ wife according to their lifestyle practices and their extents of coping behaviour during the departure of their husband.It was recommended that: Seafarer’s wife must know how to positively cope behaviourally during the different activities where they practice their personal lifestyles as well as during their husband’s departure for sail; the husband of the respondents must identify the different factors that might influence their wife’s way they coping; Shipping Industry administrators must increase their awareness in determining which part of their present programs for seafarer and their wife can be enhanced to be able to help them cope with the realities of seafaring life; Future researchers to use this study as reference.